2007
DOI: 10.3197/096327107x228409
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Vision and Mission Statements of International Environmental Organisations

Abstract: ?seq=1&cid=pdf-reference#references_tab_contents You may need to log in to JSTOR to access the linked references. JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…4 and see Table 2). However, the enthusiasm for ecosystem services as a strategy for enhancing conservation support is far outpacing credible evidence of what is possible and how to best achieve the much desired win-win outcomes.…”
Section: The Absence Of Data Jeopardizes the Success Of Future Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and see Table 2). However, the enthusiasm for ecosystem services as a strategy for enhancing conservation support is far outpacing credible evidence of what is possible and how to best achieve the much desired win-win outcomes.…”
Section: The Absence Of Data Jeopardizes the Success Of Future Projectsmentioning
confidence: 99%
“…Although these projects generally lack a formal foundation of ecosystem service science, they all are motivated by the general hypothesis that nature provides humans with benefits. In fact, an analysis of the vision and mission statements of major environmental organizations, including the major conservation nongovernmental organizations (NGOs), found that nature is typically portrayed as resources necessary for human well-being and sustainable development (4). Increasingly, the language used by conservation NGOs to discuss the value of nature is becoming more explicit in its reference to ecosystem services.…”
mentioning
confidence: 99%
“…However, assigning economic value to natural resources leads to the reclassification of nature as a set of commodities or goods, and appears to be a symptom of a global discourse McAfee (1999) calls a "post-neoliberal environment-economic paradigm" spread by efforts in sustainable development or similar "green developmentalism" projects (McAfee 1999; see also Campagna and Fernandez 2007). McAfee argues that this discourse abstracts nature from its context in the process of putting it on the market as a commodity.…”
Section: The Marine Park In Practice: Education and Capacitybuilding mentioning
confidence: 98%
“…The wide recognition of intrinsic value of by the public at large had been remarked before in the Netherlands and elsewhere (e.g. Van den Born et al, 2001), and the same mismatch between personal and organisational values was strikingly revealed by Butler and Acott (2007) in the UK and by Campagna and Fernández (2007), who have taken stock of the vision and mission statements of international environmental organisations. Both studies found that intrinsic value statements are virtually absent in the institutional statements, as if loving nature for its own sake is something to be ashamed of, even for conservation organisations.…”
Section: Values Of Naturementioning
confidence: 84%